2019
DOI: 10.1177/1747954119847171
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of game-play characteristics within-season for the National Basketball Association

Abstract: The aim of this study was to explore the (dis)similarity of game-play characteristics throughout an in-season period within the National Basketball Association. Thirteen performance-related indicators of all 1230 games of the regular 2016–2017 season in the National Basketball Association were analysed. Non-metric multidimensional scaling was used to examine (dis)similarity of team profiles. The two-dimensional multivariate matrix showed that team profiles generally presented similarity, while the beginning an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 34 publications
1
26
0
Order By: Relevance
“…The aim of the current study was to model the performance of basketball teams' match play considering match-related statistics across eight seasons, and for the most successful or dominant teams during the period under study. As the first examination of the long-term evolution of several professional basketball team's performance [17], the current findings indicated that most match-related performance indicators failed to evolve over time, except for 3-point field goals and assists (2012-2017) which increased while 2-point field goals (2013-2016) decreased. In particular, these indicators reflected the growing impact of shot selection on ball possessions and match outcome [5,12].…”
Section: Discussionmentioning
confidence: 67%
See 4 more Smart Citations
“…The aim of the current study was to model the performance of basketball teams' match play considering match-related statistics across eight seasons, and for the most successful or dominant teams during the period under study. As the first examination of the long-term evolution of several professional basketball team's performance [17], the current findings indicated that most match-related performance indicators failed to evolve over time, except for 3-point field goals and assists (2012-2017) which increased while 2-point field goals (2013-2016) decreased. In particular, these indicators reflected the growing impact of shot selection on ball possessions and match outcome [5,12].…”
Section: Discussionmentioning
confidence: 67%
“…A multivariate analytical method was used to uncover dynamical trends of the team performance indicators [17]. Multivariate methods were chosen as they enabled the mapping of the entire team match styles rather than individual indicators that determine inferences based upon sets of models [21].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations